The eurozone: What is to be done? - Patrick Minford; Zhirong Ou; Michael R. Wickens; Zheyi Zhu (Cardiff University, Cardiff Business School, 2021)
We construct a macro DSGE model of the eurozone and its two main regions, the North and the South, with the aim of matching the macro facts of these economies by indirect inference and using the resulting empirically-based model to assess possible new policy regimes. The model we have found to fit the facts suggests that substantial gains in macro stability and consumer welfare are possible if the fiscal authority in each region is given the freedom to respond to its own economic situation. Further gains could come with the restoration of monetary independence to the two regions, in effect creating a second 'southern euro' bloc.
Keywords: E32; E52; E62; F41; 330; eurozone; macro stability; fiscal policy; monetary independence